Prevention of voltage instability in radial distribution system during fault occurrence - baqer Turki Atiyah, Dr (International Journal of Engineering and Technology, 2018)
One of the most important fundamentals required for the rapid progress of technology, is stability in power systems. Therefore, with the power systems used for transfering energy over long distances, alongside the exposure of natural phenomena and errors, the stability of voltage protection becomes a necessity for economic and occupational safety reasons. In this paper, the analysis of the level of the voltage of the distribution network was studied by linking the capacitor bank after the network was exposed to error. A study was carried out for the compacted dynamic after connecting the capacitor bank. A PSCAD program was used to simulate a complete electrical distribution system and test results were taken from the same program.Â Â